1989
DOI: 10.1111/j.1365-2044.1989.tb09196.x
|View full text |Cite
|
Sign up to set email alerts
|

Postoperative analgesia for haemorrhoidectomy

Abstract: SummaryThis study compared

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

1994
1994
2010
2010

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(2 citation statements)
references
References 6 publications
0
2
0
Order By: Relevance
“…Local anesthesia allows immediate surgery for acute thrombosed prolapsed internal hemorrhoids [11]in pregnancy or advanced age [12]. A short-range local anesthesia (lidocaine) combined with a long-range local agent (marcaine with adrenalin) [13, 14]allows the patient’s immediate discharge at the end of surgery [10]. …”
Section: Discussionmentioning
confidence: 99%
“…Local anesthesia allows immediate surgery for acute thrombosed prolapsed internal hemorrhoids [11]in pregnancy or advanced age [12]. A short-range local anesthesia (lidocaine) combined with a long-range local agent (marcaine with adrenalin) [13, 14]allows the patient’s immediate discharge at the end of surgery [10]. …”
Section: Discussionmentioning
confidence: 99%
“…The use of neuronal blockade for surgery is effective for postoperative pain and has an opioid‐sparing effect ( 27). Different infiltration techniques have been shown to be pain reducing and opioid sparing after cholecystectomy ( 28), inguinal hernia repair ( 29), breast surgery ( 30), gynaecological laparotomies ( 31), orthopaedic ( 32) and anorectal ( 33) surgery. A recent study has also shown beneficial effect from infiltration of local anaesthesia in the trocar entrances after laparoscopic procedures ( 34).…”
Section: Principles Of Postoperative Analgesia: What Are the Issues?mentioning
confidence: 99%